The Inhibitory Effect of Lysophosphatidylcholine on Proangiogenesis of Human CD34+ Cells Derived Endothelial Progenitor Cells - Zhao, Haijun; He, Yanhui (Frontiers in Molecular Biosciences, 2021)
Increasing evidence reveals that lysophosphatidylcholine (LPC) is closely related to endothelial dysfunction. The present study aimed to investigate the mechanism of LPC in inhibiting the proangiogenesis and vascular inflammation of human endothelial progenitor cells (EPCs) derived from CD34+ cells. The early EPCs were derived from CD34+ hematopoietic stem cells whose purity was identified using flow cytometry analysis. The surface markers (CD34, KDR, CD31; VE-cadherin, vWF, eNOS) of EPCs were examined by flow cytometry analysis and immunofluorescence. RT-qPCR was used to detect the mRNA expression of inflammatory cytokines (CCL2, IL-8, CCL4) and genes associated with angiogenesis (VEGF, ANG-1, ANG-2) in early EPCs after treatment of LPC (10 μg/mL) or phosphatidylcholine (PC, 10 μg/mL, control). The angiogenesis of human umbilical vein endothelial cells (HUVECs) incubated with the supernatants of early EPCs was detected by a tube formation assay. The mRNA and protein levels of key factors on the PKC pathway (phosphorylated PKC, TGF‑β1) were measured by RT-qPCR and western blot. The localization of PKC-β1 in EPCs was determined by immunofluorescence staining. We found that LPC suppressed the expression of CCL2, CCL4, ANG-1, ANG-2, promoted IL-8 expression and had no significant effects on VEGF expression in EPCs. EPCs promoted the angiogenesis of HUVECs, which was significantly inhibited by LPC treatment. Moreover, LPC was demonstrated to promote the activation of the PKC signaling pathway in EPCs. In conclusion, LPC inhibits proangiogenesis of human endothelial progenitor cells derived from CD34+ hematopoietic stem cells.